2013
DOI: 10.1111/cxo.12002
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of corneal thickness using SOCT Copernicus HR

Abstract: Purpose: The aim of this study is to determine the reliability of corneal thickness measurements derived from SOCT Copernicus HR (Fourier domain OCT). Methods: Thirty healthy eyes of 30 subjects were evaluated. One eye of each patient was chosen randomly. Images were obtained of the central (up to 2.0 mm from the corneal apex) and paracentral (2.0 to 4.0 mm) cornea. We assessed corneal thickness (central and paracentral) and epithelium thickness. The intra-observer repeatability data were analysed using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Several reports have showed repeatability and reproducibility results of various OCT systems for corneal pachymetry, which are summarized in Table 3 [4,22,24,40,41,[49][50][51][52]. Our results showed a CoR of less than 3.54 μm for normal subjects and 3.78 μm for post-LASIK patients within the central zone (0-2 mm) and the paracentral zone (2-5 mm) for corneal thickness repeatability and reproducibility.…”
Section: Discussionsupporting
confidence: 58%
“…Several reports have showed repeatability and reproducibility results of various OCT systems for corneal pachymetry, which are summarized in Table 3 [4,22,24,40,41,[49][50][51][52]. Our results showed a CoR of less than 3.54 μm for normal subjects and 3.78 μm for post-LASIK patients within the central zone (0-2 mm) and the paracentral zone (2-5 mm) for corneal thickness repeatability and reproducibility.…”
Section: Discussionsupporting
confidence: 58%
“…There were a few studies in the literature that evaluated the reproducibility of central corneal ET measurements. 8-9, 12-13 In this study, we evaluated the repeatability of corneal ET and CT measurements at the center, paracentral and peripheral zones in normal and LASIK eyes using the RTVue.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Fourier domain based device SOCT Copernicus HR, in 30 healthy eyes, Vidal et al 8 found that repeatability for corneal epithelial measurements was poor with ICC value of 0.391. In contrast, the ICC values for central corneal ET found in current study using the RTVue were >0.98.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The intraobserver reproducibility of FD-OCT (SOCT Copernicus HR, Optopol, Poland) was substantial to almost perfect for automatically measured CT but only fair (ICC = 0.391) for manually assessed ET. 9 FD-OCT (Cirrus HD-OCT, Zeiss, Germany) presented an excellent intraobserver and interobserver reproducibility of ET and CT measured at the vertex. 10 In a retrospective study, Ma et al 5 reported an excellent intraobserver repeatability for ET and CT measured with the RTVue in 17 corneal zones in healthy and post-LASIK eyes.…”
mentioning
confidence: 99%